Adrenal Hormone and Metabolic Biomarker Responses to 30 min of Intermittent Cycling Exercise in Breast Cancer Survivors - Evans, E. S.; Hackney, A. C.; Pebole, M. M.; McMurray, R. G.; Muss, H. B.; Deal, A. M.; Battaglini, C. L. (International Journal of Sports Medicine, 2016)
The aim of this study was to explore the effect of one bout of aerobic exercise on epinephrine, norepinephrine, cortisol, glucose, lactate, and free fatty acid (FFA) responses in breast cancer survivors and healthy controls. 9 female breast cancer survivors and 9 women without a history of cancer completed 30 min of cycle ergometry exercise at 60% of VO2peak. Blood samples were taken pre-exercise, immediately post-exercise, and 2 h post-exercise from which plasma concentrations of study variables were measured. Immediately and 2 h post-exercise, increases were observed in epinephrine (control group only) norepinephrine (both groups), lactate (both groups), and FFA (both groups immediately post-exercise; breast cancer survivor group only at 2 h post-exercise) (p<0.05). Cortisol decreased immediately and 2 h post-exercise in the control group while glucose decreased immediately post-exercise in the breast cancer survivor group (p<0.05). In conclusion, breast cancer survivors appeared to display attenuated epinephrine, cortisol, and lactate responses while displaying larger magnitude changes in glucose and FFA responses compared to controls. These preliminary findings may have implications for the regulation of metabolism during exercise in breast cancer survivors.
Keywords: acute aerobic exercise; stress hormones; energy metabolism; oncology patients